Startups: a systematic review of literature and future research directions - Silva, Luciana Santos Costa Vieira da; Kaczam, Fabíola; Dantas, Anderson de Barros; Janguia, Josenilde Mario (Revista de Ciencias de la Administración, 2021)
The objective of the research is to map the literature based on a Systematic Literature Review on the theme of startups and to highlight some theoretical gaps based on publications of high-reputation scientific journals. The period from 1990 to 2019 was defined for the elaboration of this study. We use the excel spreadsheet, in addition to the HistCite ™, VOSviewer, IRATUMEQ, and R Studio packages. The results show that the typology of the startups evaluated, after reading 68% of the articles, organizations are characterized as a group of new companies, that is, relatively young and inexperienced when compared to the most stable and mature in organizational development. They refer to those that are in the initial stage and are susceptible to the influence of various factors, such as investors, supplier customers, partners, etc., and should think strategically about how to act and, this concerns a group of dynamic startups that work with innovations.